Fetal MRI: A pictorial essay - Rathee, Sapna; Joshi, Priscilla; Kelkar, Abhimanyu; Seth, Nagesh (Indian Journal of Radiology and Imaging, 2016)
Ultrasonography (USG) is the primary method for antenatal fetal evaluation. However, fetal magnetic resonance imaging (MRI) has now become a valuable adjunct to USG in confirming/excluding suspected abnormalities and in the detection of additional abnormalities, thus changing the outcome of pregnancy and optimizing perinatal management. With the development of ultrafast sequences, fetal MRI has made remarkable progress in recent times. In this pictorial essay, we illustrate a spectrum of structural abnormalities affecting the central nervous system, thorax, genitourinary and gastrointestinal tract, as well as miscellaneous anomalies. Anomalies in twin gestations and placental abnormalities have also been included.
Keywords: Anomalies; congenital; fetal magnetic resonance imaging; ultrasonography